The 46th Reconnaissance Squadron: Arctic Exploration and Questions of Sovereignty in the Early Cold War - Murray, David (The Northern Mariner / Le marin du nord, 2022)
In the early Cold War, the Arctic emerged as a key region in American military planning. In 1946, the newly formed US Strategic Air Command deployed the 46th Reconnaissance Squadron to Alaska to improve navigational and cold weather flying capabilities. Major projects assigned to the squadron included the search for undiscovered land masses in the polar region, should any exist, and the establishment of an air route between Ladd Airfield, Alaska and the US base at Meeks Field, Iceland, which involved overflights of the Canadian Arctic Archipelago. This paper will explore the core projects within this initiative and how the US sought to manage Canadian sovereignty interests as it pursued its strategic objectives against the Soviet Union. Au début de la Guerre froide, l’Arctique est devenu une région clé de la planification militaire américaine. En 1946, le nouveau Strategic Air Command des États-Unis a déployé le 46e escadron de reconnaissance en Alaska pour améliorer les capacités de navigation et de vol par temps froid. Les principaux projets assignés à l’escadron comprenaient la recherche de masses terrestres non découvertes dans la région polaire, s’il en existait, et l’établissement d’une route aérienne entre l’aérodrome de Ladd, en Alaska, et la base américaine de Meeks Field, en Islande, qui supposait des survols de l’Archipel arctique canadien. Cet article étudie les principaux projets de cette initiative et les efforts déployés par les États-Unis pour gérer les intérêts de souveraineté du Canada alors qu’ils poursuivaient leurs objectifs stratégiques contre l’Union soviétique.